ГРИГОРІЙ САВИЧ СКОВОРОДА. УКРАЇНСЬКИЙ ФІЛОСОФ, ПЕДАГОГ, ПРОСВІТИТЕЛЬ - Зорик, В. А. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
У цій статті автор прагне дослідити і показати педагогічну діяльність Г.Сковороди на основі матеріалів і першоджерел. Стаття буде корисна як для студентів і аспірантів, так і для тих, хто займається вивченням спадщини великого українського філософа і просвітителя. В.А. Зорик ГРИГОРИЙ САВИЧ СКОВОРОДА. УКРАИНСКИЙ ФИЛОСОФ, ПЕДАГОГ, ПРОСВЕТИТЕЛЬ В этой статье автор стремится исследовать и показать педагогическую деятельность Г.Сковороды на основе материалов и первоисточников. Статья будет полезна как для студентов и аспирантов, так и для тех, кто занимается изучением наследия великого украинского философа и просвитителя. Ключевые слова: педагогика, просветительство, мир, духовность, Библия, идеализм, мировозрение. THE PEDAGOGICS OF G.I. SKOVORODA V. Zorik It this article the author attempts himself to investigate and to show the pedagogical activity of G.Skovoroda on the basis of materials and the ultimate sources. This work will be useful both for the students and the graduate students and for the those who deal with the study of the heritage of great Ukrainian philosopher and enlightener. Key words: pedagogics, enlightment, spirituality, Bible, idealism, world view, pantheism.